Association between tunneled pleural catheter use and infection in patients immunosuppressed from atineoplastic therapy: a multicenter study - Wilshire, Candice L.; Chang, Shu-Ching; Gilbert, Christopher R.; Akulian, Jason A.; AlSarraj, Mohammed K.; Asciak, Rachelle; Bevill, Benjamin T.; Davidson, Kevin R.; Delgado, Ashley; Grosu, Horiana B.; Herth, Felix; Lee, Hans J.; et al. (Annals of the American Thoracic Society, 2021)
Rationale: Patients with malignant or paramalignant pleural effusions (MPEs or PMPEs) may have tunneled pleural catheter (TPC) management withheld because of infection concerns from immunosuppression associated with antineoplastic therapy.Objectives: To determine the rate of infections related to TPC use and to determine the relationship to antineoplastic therapy, immune system competency, and overall survival (OS).Methods: We performed an international, multiinstitutional study of patients with MPEs or PMPEs undergoing TPC management from 2008 to 2016. Patients were stratified by whether or not they underwent antineoplastic therapy and/or whether or not they were immunocompromised. Cumulative incidence functions and multivariable competing risk regression analyses were performed to identify independent predictors of TPC-related infection. Kaplan-Meier method and multivariable Cox proportional hazards modeling were performed to examine for independent effects on OS.Results: A total of 1,408 TPCs were placed in 1,318 patients. Patients had a high frequency of overlap between antineoplastic therapy and an immunocompromised state (75-83%). No difference in the overall (6-7%), deep pleural (3-5%), or superficial (3-4%) TPC-related infection rates between subsets of patients stratified by antineoplastic therapy or immune status was observed. The median time to infection was 41 (interquartile range, 19-87) days after TPC insertion. Multivariable competing risk analyses demonstrated that longer TPC duration was associated with a higher risk of TPC-related infection (subdistribution hazard ratio, 1.03; 95% confidence interval [CI], 1.00-1.06; P = 0.028). Cox proportional hazards analysis showed antineoplastic therapy was associated with better OS (hazard ratio, 0.84; 95% CI, 0.73-0.97; P = 0.015).Conclusions: The risk of TPC-related infection does not appear to be increased by antineoplastic therapy use or an immunocompromised state. The overall rates of infection are low and comparable with those of immunocompetent patients with no relevant antineoplastic therapy. These results support TPC palliation for MPE or PMPEs regardless of plans for antineoplastic therapy.